Understanding Level of Farmers on the Use of The Integrated Livestock Area in Nggorang Village, Komodo District, West Manggarai in East Nusa Tenggara - Detha, Annytha; Foeh, Nancy; Ndaong, Nemay; Maranatha, Grace; Datta, Frans Umbu (International Journal of Community Service Learning, 2019)
The purpose of this community service activity is to support the Agro Tourism of Nggorang Village, Komodo District, West Manggarai to maximize the productivity of cattle farms by utilizing the availability of natural resources while empowering rice straw agricultural waste as the main source of feed by utilizing feed processing technology, creating a healthy environment in the village by supporting Agroeduwisata village and clean grazing center through the utilization of livestock feces waste into organic fertilizer using natural probiotics, which have an impact on environmental cleanliness. In achieving this goal, there are a number of methods for achieving the objectives, namely the active participation approach of the community in collaboration with the village component starting from the planning stage, including data collection and mapping of available resources; implementation phase; the monitoring and evaluation phase of the activities to ensure the achievement of all aspect of the objectives. Based on the results obtained in this activity, there is an understanding of the benefits and advantages of integrated grazing land that can be applied by farmers in Desa Nggorang village, Komodo District, West Manggarai in NTT  Keywords: Livestock centers; Agro-tourism; Komodo district